Ultrasound-assisted Strecker synthesis of novel 2-(hetero)aryl-2-(arylamino)acetonitrile derivatives - Gal, Emese; Gaina, Luiza; Petkes, Hermina; Pop, Alexandra; Cristea, Castelia; Barta, Gabriel; Vodnar, Dan Cristian; Silaghi-Dumitrescu, Luminiţa (Beilstein Journal of Organic Chemistry, 2020)
This work describes an efficient, simple, and ecofriendly sonochemical procedure for the preparation of new α-(arylamino)acetonitrile derivatives C-substituted with phenothiazine or ferrocene units. The synthetic protocol is based on the Strecker reaction of a (hetero)aryl aldimine substrate with trimethylsilyl cyanide (TMSCN) in poly(ethylene glycol) (PEG) solution. The advantages of the sonochemical versus the conventional α-(arylamino)acetonitrile synthesis are the significantly shorter reaction time (30 min instead of 72 hours), the higher purity and the easier separation of the product that precipitated from the reaction mixture in crystalline form as depicted by scanning electron microscopy (SEM) analysis. The single crystal X-ray diffraction analysis disclosed the arrangement of the α-(arylamino)acetonitrile molecules in the aggregated crystalline state as a racemic mixture. The mutagenic/antimutagenic potential for three representative derivatives containing phenothiazinyl, ferrocenyl, and phenyl units, respectively, was evaluated by the Ames Salmonella/microsome test using S. typhimurium TA98 and TA100 strains with and without metabolic activation. The preliminary screening results pointed out that the C-(hetero)aryl-α-(arylamino)acetonitrile derivatives can be considered genotoxically safe and possibly antimutagenic.
Keywords: Ames test; α-aminoacetonitriles; ferrocene; phenothiazine; SEM; single crystal XRD; sonochemistry